Assessing The Quality Of The Ruang Guru Application Among High School Students Using The Delon And Mclean Model Approach - Marlin, Revina; Veri, Jhon (Journal of Science Education and Management Business, 2025)
Ruangguru application is designed to explore the effectiveness of the ruangguru application in improving the educational experience of high school students. The quality of the application helps provide satisfaction for the organization and increases competitiveness, providing added value to high school students. To measure the success of an application, the Delone and McLean success model can be applied. By testing the system using DeLone and McLean, it is known that the quality of the ruangguru application has very good quality, namely with a score of 100%